2009
DOI: 10.1007/bf03342707
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ownership on Hospital Efficiency in Germany

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 62 publications
4
80
0
2
Order By: Relevance
“…Watcharasriroj and Tang (2004) used DEA to measure the technical efficiency of 92 public nonprofit hospitals in Thailand and found that large hospitals (at least 500 beds) significantly operate more efficiently than smaller hospitals and IT positively contributes to the efficiency for both large and small hospitals. Tiemann and Schreyögg (2009) Asmild et al (2013) recently studied the productive efficiency of 141 public hospitals in two Canadian provinces and found that the hospitals in the larger, more urban areas consistently outperform their counterparts in the smaller, more rural area in terms of technical efficiency. Chul-Young et al also (2013) concluded that hospital size significantly influences performance.…”
Section: Discussionmentioning
confidence: 99%
“…Watcharasriroj and Tang (2004) used DEA to measure the technical efficiency of 92 public nonprofit hospitals in Thailand and found that large hospitals (at least 500 beds) significantly operate more efficiently than smaller hospitals and IT positively contributes to the efficiency for both large and small hospitals. Tiemann and Schreyögg (2009) Asmild et al (2013) recently studied the productive efficiency of 141 public hospitals in two Canadian provinces and found that the hospitals in the larger, more urban areas consistently outperform their counterparts in the smaller, more rural area in terms of technical efficiency. Chul-Young et al also (2013) concluded that hospital size significantly influences performance.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate (mort) is used as a proxy for (poor) quality of care (e.g. [39,41,46]). Hospitals with a relatively large budget might have more slack resources than hospitals with less financial means [7].…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…The measure is defined as the radial distance of the i-th hospital to the frontier function, which is determined by means of a linear combination of the best practicing (efficient) units. We assume variable returns to scale to allow that hospitals operate at an inefficient scale size [24,46]. To compare hospitals with distinct exogenously fixed input variables we account for non-discretionary input variables (Banker and Morey [3], for details see Appendix A.1).…”
Section: Non-parametric Ef F Iciency Measurementmentioning
confidence: 99%
See 2 more Smart Citations